Stent-graft implantation for late postpancreatectomy hemorrhage after pancreatoduodenectomy - Xiaoye Li; Shibo Xia; Liangxi Yuan; Lei Zhang; Chao Song; Xiaolong Wei; Qingsheng Lu (Chinese Journal of Traumatology)
Purpose: Postpancreatectomy hemorrhage (PPH) is a life-threatening complication after pancreatoduodenectomy. Stent-graft implantation is an emerging treatment option for PPH. This study reports the outcome of PPH treated with stent-graft implantation. Methods: This was a single-center, retrospective study. Between April 2020 and December 2023, 1723 pancreatectomy cases were collected while we screened 12 cases of PPH after pancreatoduodenectomy treated with stent-graft implantation. Patients' medical and radiologic images were retrospectively reviewed. Technical and clinical success, complications, and stent-graft patency were evaluated. Continuous data are reported as means ± standard deviation when normally distributed or as median (Q1, Q3) when the data is non-normal distributed. Categorical data are reported as n (%). A p < 0.05 was considered statistically significant. Kaplan-Meier estimates were used for stent patency and patients’ survival. Results: Pancreatic fistula was identified in 6 cases (50.0%), and pseudoaneurysm was identified in 3 cases (25.0%), including pancreatic fistula together with pseudoaneurysm in 1 case (8.3%). All pseudoaneurysm or contrast extravasation sites were successfully excluded with patent distal perfusion, thus technical success was achieved in all cases. The overall survival rate at 6 months and 1 year was 91.7% and 78.6%, respectively. One patient had herniation of the small intestine into the thoracic cavity, which caused a broad thoracic and abdominal infection and died during hospitalization. Rebleeding occurred at the gastroduodenal artery stump in 1 case after stent-graft implantation for the splenic artery and was successfully treated with another stent-graft implantation. Two cases of asymptomatic stent-graft occlusion were observed at 24.6 and 26.3 after the operation, respectively. Conclusions: With suitable anatomy, covered stent-graft implantation is an effective and safe treatment option for PPH with various bleeding sites and causes.